Perfil Lipídico, Antropométrico Y De Condición Física De Los Estudiantes Pertenecientes A La Selección De Fútbol De La Universidad Del Quindío (2015)
Soccer is one of the most practiced sports at the global level. In the Universidad Del Quindio there are students that conform the male and female soccer team, however, although in general they present good results in the competences, is unknown how is the lipid profile, antropometric characteristics and health condition of these sportsmen. Objective: Establish the lipid profile, antropometric characteristics and health condition of the students belonging to the male and female soccer team of the Universidad delQuindio. Methodology: This research work was quantitative, descriptive, cross-sectional and was performed on the students belonging to the male and female soccer team of the Universidad del Quindio. The population consisted of 38 subjects ( 16 male subjects and 22 female subjects ). To measure the lipid profile they were used commercial kits, following the manufacturer’s instructions. The antropometric assessment was performed following the indications of the International Society for the Advancement of Kinanthropometry (ISAK) and for the determination of physical capabilities of the sportsmen, they were used the Wells’s test, the Legger’s test, the 30 meters acceleration test and the horizontal jump. The results of the investigation show that the average of BMI ( body mass index ) it is within normal. The waist-to-hip ratio shows that the women have a high cardiovascular risk. With respect to the lipid profile of the general population it was determined that the Total Cholesterol, Triglycerides, Arterial Index, HDL, LDL and VLDL they were within the desirable range, finding some sportsmen with a few of abnormal values. About fat percentage it can say that men have over-weight. The muscular percentage, the bone percentage, the residual percentage and the skin percentage were those indicated in both men and women. The predominant kind of somatotype in men it was the balanced mesomorfo. In the women case the predominant kind of somatotype it was the endo-mesomorfo. At observing flexibility was found that in average this was higher in women than in men. Conclusions: In general, the most of the evaluated data they were within normal levels, with some sportsmen that have a few abnormal levels that we must work to improve.